A New Model of Manufacturer's Optimal Product Supply Strategy in the Context of Precision Marketing: Based on Real Demand Pattern. (21st December 2020) - Zhuo, Zhiyi; Chen, Shuhong; Chau, Ka Yin
Abstract : Precision marketing has a crucial impact on whether a manufacturer can make the most profit. This paper conducts precision marketing based on customer demand and analyzes how developers should formulate the quantity and pricing of products to obtain optimal profit in the case of real demand of customers. First, the research status of the development of precision marketing and its demand for its theoretical influence is introduced. Secondly, an appropriate real demand function is constructed, according to the characteristics of the product and consumer positioning, combined with the expression of the demand function in economics. Thirdly, by using the constructed "real demand" function and combining the basic knowledge of optimization and probability theories, the profit function for manufacturers in "real demand" pattern is established. When the manufacturer wishes to obtain optimal profit from three different sales models, the product manufacturing quantity and pricing are analyzed. Finally, an example is given to verify the results of the previous analysis.